Combined dehydrogenation of glycerol with catalytic transfer hydrogenation of H2 acceptors to chemicals: Opportunities and challenges - Zhang, Guangyu; Zhao, Jian; Jin, Xin; Qian, Yanan; Zhou, Mingchuan; Jia, Xuewu; Sun, Feng; Jiang, Jie; Xu, Wei; Sun, Bing (Frontiers in Chemistry, 2022)
Catalytic transformation of low-cost glycerol to value-added lactic acid (LA) is considered as one of the most promising technologies for the upgradation of glycerol into renewable products. Currently, research studies reveal that anaerobic transformation of glycerol to LA could also obtain green H2 with the same yield of LA. However, the combined value-added utilization of released H2 with high selectivity of LA during glycerol conversion under mild conditions still remains a grand challenge. In this perspective, for the first time, we conducted a comprehensive and critical discussion on current strategies for combined one-pot/tandem dehydrogenation of glycerol to LA with catalytic transfer hydrogenation of H2 acceptors (such as CO2) to other chemicals. The aim of this overview was to provide a general guidance on the atomic economic reaction pathway for upgrading low-cost glycerol and CO2 to LA as well as other chemicals.